Wife Abuse prevalence, reason and coping. - Sadian, Ruth Edisel Rylle B. (Tacloban City Ruth Edisel Rylle Sadian, 2011)
This study was conducted within the six barangays of MacArthur, Leyte. A total of 97 abused wives served as respondents of this study. A 17-item interview schedule was administered to determine the prevalence of abuse, reasons of abuse and coping strategies of the victims. The results showed that boxing is the most prevalent form of physical abuse with 43.3% while insulting is the most perpetrated form of psychological abuse accounting to 96.91% of the respondents. A significant number of respondents have experienced forced sexual intercourse and are prohibited by their husband to hold a job. It was also revealed that 85.57% are aware of their rights as a woman. Nevertheless, 59.79% of the abused women do not do anything against the abuse. The abuse is perpetrated any time of the day and the home is not the safest place for an abused wife. Abused wives have given varied reasons for the abuse and have different styles of coping.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban.
Keywords: Social Science